Guidelines for the testing and reporting of cytogenetic results for risk stratification of multiple myeloma: a report of the Cancer Genomics Consortium Plasma Cell Neoplasm Working Group - Xinyan Lu; Erica F. Andersen; Rahul Banerjee; Celeste C. Eno; Patrick R. Gonzales; Shaji Kumar; Angela M. Lager; Patricia M. Miron; Trevor Pugh; Fabiola Quintero-Rivera; Virginia C. Thurston; Daynna J. Wolff; et al. (Blood Cancer Journal)
Abstract Fluorescence in situ hybridization (FISH) remains the gold-standard clinical assay to detect genetic abnormalities in multiple myeloma (MM). However, FISH panel design, use of conventional chromosome banding analysis and reporting practices have been reported to vary among laboratories. Therefore, standardization in FISH testing and reporting practices is needed to improve report clarity and avoid misinterpretation. The recommendations in this paper represent a consensus of our Cancer Genomics Consortium Plasma Cell Neoplasm Working Group, comprising a joint panel of cytogenetic laboratory directors and clinical investigators with expertise in the diagnosis, risk stratification, and treatment of multiple myeloma. Prior to developing these consensus recommendations, we performed a full literature review and conducted a survey of 102 oncologists to assess current variations and challenges in MM cytogenetic/FISH testing and reporting. Our guidelines establish best practices for the optimization of FISH panel selection, and recommendations for standardized reporting of cytogenetic results to align with the 2025 International Myeloma Society (IMS)/International Myeloma Working Group (IMWG) Updated Risk Stratification.